The Idea-Driven Organization Unlocking the Power in Bottom-Up Ideas - Robinson, Alan G. (Berrett-Koehler Publishers, 2014)
Too many organizations are overlooking, or even suppressing, their single most powerful source of growth and innovation. And it's right under their noses. The frontline employees who interact directly with your customers, make your products, and provide your services have unparalleled insights into where problems exist and what improvements and new offerings would have the most impact. In this follow-up to their bestseller Ideas Are Free, Alan G. Robinson and Dean M. Schroeder show how to align every part of an organization around generating and implementing employee ideas and offer dozens of examples of what a tremendous competitive advantage this can offer. Their advice will enable leaders to build organizations capable of implementing 20, 50, or even 100 ideas per employee per year. Citing organizations from around the world, they explain what's needed to put together a management team that can lead the type of organization that embraces grassroots ideas and describe the strategies, policies, and practices that enable them. They detail exactly how high-performing idea processes work and how to design one for your organization. There's constant pressure today to do more with less. But cutting wages and benefits and pushing people to work harder with fewer resources can go only so far. Ironically, the best solution resides with the very people who have been bearing the brunt of these measures. With Robinson and Schroeder's advice, you can unleash a constant stream of great ideas that will strengthen every facet of your organization